Parties du corps et approche orientee objets - Grigowicz, Anna (Neophilologica, 2004)
In this article the author discusses a method of lexicographic description which uses G. Gross’s concept of object classes, ontological classification in the WordNet style, B. Boguraev and J. Pustejovsky’s qualia structure, computer lexicography and automatic translation. The author focuses herself on the “object-oriented” approach to the proposed descriptions and adopts this approach to her analysis of the chosen names of body parts in French. The category of body parts, established on the basis of the ontological features of its elements, can be treated as an object class. This conclusion is justified by the fact that two operators: avoir mal and soigner, which characterize every object of the category under analysis, allow us to treat this category as an object class in the object-oriented approach.